Enhancing monitoring and transboundary collaboration for conserving migratory species under global change: The priority case of the red kite. (1st September 2022) - Mattsson, Brady J.; Mateo-Tomás, Patricia; Aebischer, Adrian; Rösner, Sascha; Kunz, Florian; Schöll, Eva M.; Åkesson, Susanne; De Rosa, Davide; Orr-Ewing, Duncan; Bodega, David de la; Ferrer, Miguel; Gelpke, Christian; et al.
Abstract: Calls for urgent action to conserve biodiversity under global change are increasing, and conservation of migratory species in this context poses special challenges. In the last two decades the Convention on the Conservation of Migratory Species of Wild Animals (CMS) has provided a framework for several subsidiary instruments including action plans for migratory bird species, but the effectiveness and transferability of these plans remain unclear. Such laws and policies have been credited with positive outcomes for the conservation of migratory species, but the lack of international coordination and on-ground implementation pose major challenges. While research on migratory populations has received growing attention, considerably less emphasis has been given to integrating ecological information throughout the annual cycle for examining strategies to conserve migratory species at multiple scales in the face of global change. We fill this gap through a case study examining the ecological status and conservation of a migratory raptor and facultative scavenger, the red kite ( Milvus milvus ), whose current breeding range is limited to Europe and is associated with agricultural landscapes and restricted to the temperate zone. Based on our review, conservation actions have been successful at recovering red kite populations within certain regions. Populations however remain depleted along the southern-most edge of the geographic range where many migratory red kites from northern strongholds overwinter. This led us to a forward-looking and integrated strategy that emphasizes international coordination involving researchers and conservation practitioners to enhance the science-policy-action interface. We identify and explore key issues for conserving the red kite under global change, including enhancing conservation actions within and outside protected areas, recovering depleted populations, accounting for climate change, and transboundary coordination in adaptive conservation and management actions. The integrated conservation strategy is sufficiently general such that it can be adapted to inform conservation of other highly mobile species subject to global change. Highlights: Plans to conserve migratory species must account for global environmental changes. We review conservation status and actions for a raptor across the annual cycle. Actions enabled red kite populations to recover except along southern edge of range. We develop an integrated strategy emphasizing international coordination. The integrated framework can be adapted for other highly mobile species.